NUMERICAL STUDY OF PRESSURE DROP AND FLUID FRICTION IN LAMINAR FLOW RECTANGULAR MICRO-CHANNELS - Hasan, Hayder Mohammed (Basrah Journal for Engineering Sciences, 2014)
An incompressible three dimensional continuity and Navier-Stokes (momentum equations) equations are numerically solved to obtain the pressure drop and fluid friction in laminar steady state micro-channel flow of water. The governing equations are solved by using SIMPLE algorithm with finite volume method and FORTRAN code to obtain pressure field in rectangular micro-channel and then from the pressure field both friction factor f and friction constant Cf are obtained. The results showed that the factors affecting the pressure drop, friction factor f and friction constant Cf are; channel length L, Reynolds number Re, aspect ratio a, channel volume Vch and hydraulic diameter Dh. Increasing of channel length L leads to increase each pressure drop, f and Cf. On other hand, increasing of Re leads to increase pressure drop and decrease the f, while the Cf increase with low value of Re (Re less than 50) and then nearby with approximately constant value. Moreover, increasing of a, Vch and Dh separately leads to decrease pressure drop and increase both f and Cf.